2022
DOI: 10.3390/molecules27196282
|View full text |Cite
|
Sign up to set email alerts
|

Sodium β-Diketonate Glyme Adducts as Precursors for Fluoride Phases: Synthesis, Characterization and Functional Validation

Abstract: Very few sodium complexes are available as precursors for the syntheses of sodium-based nanostructured materials. Herein, the diglyme, triglyme, and tetraglyme (CH3O(CH2CH2O)nCH3, n = 2–4) adducts of sodium hexafluoroacetylacetonate were synthesized in a single-step reaction and characterized by IR spectroscopy, 1H, and 13C NMR. Single-crystal X-ray diffraction studies provide evidence of the formation of the ionic oligomeric structure [Na4(hfa)6]2−•2[Na(diglyme2]+ when the diglyme is coordinated, while a mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…The NMR spectra of “Pb(hfa) 2 ·glyme” complexes 1–4 have been recorded in CD 3 CN; the complete signal attribution is reported in Table 2. The spectra clearly show the signal of both the polyether moieties and the hfa anions, as previously reported for similar complexes; 61,64 neither the 1 H nor the 13 C spectra show evidence of tautomeric equilibria for the hfa moieties: the anionic enolate form is the only species observed in a solution for all the adducts.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The NMR spectra of “Pb(hfa) 2 ·glyme” complexes 1–4 have been recorded in CD 3 CN; the complete signal attribution is reported in Table 2. The spectra clearly show the signal of both the polyether moieties and the hfa anions, as previously reported for similar complexes; 61,64 neither the 1 H nor the 13 C spectra show evidence of tautomeric equilibria for the hfa moieties: the anionic enolate form is the only species observed in a solution for all the adducts.…”
Section: Resultssupporting
confidence: 79%
“…[57][58][59][60][61] Lead β-diketonates are used as precursors in vapor phase processes, such as the case of Pb(tmhd) 2 [(H-tmhd = 2,2,6,6-tetramethyl-3,5-heptanedione)], Pb(acac) 2 , [(H-acac = 2,4-pentanedione)], and their derivatives. 56,62 It has been demonstrated that glymes, through oxygen-ion complexation, are very important for the stabilization of alkaline, 61,63,64 alkaline-earth 65,66 and rare-earth 67 metals. The presence of such a class of multidentate ligands, in fact, permits also to fine-tune the properties of the final metal adducts in terms of thermal stability, moisture-and air-sensitivity, solubility, and volatility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chelation replaces multiple monodentate ligands (such as carbonates in conventional battery electrolytes) coordinating with the alkali metal ion with a single moiety (in this case, glyme), which is entropically favored. This translates into higher coordination numbers compared to typical carbonate solvents. , Previous studies have shown that glyme-based solvents with sodium salts have two glyme molecules complexing with the cation in the case of diglyme and triglyme systems, and one to two distinct glyme molecules in the solvation shells of tetraglyme systems . The chelating effect is particularly pronounced in longer glymes resulting in increased oxidative stability. ,, Electronic structure calculations show that the interactions between metal cations and the oxygen atoms of glymes lead to a notable reduction in the highest occupied molecular orbital (HOMO) energy levels of glymes. , Furthermore, glymes also have the excellent property of cointercalation with Na ions into graphite, directly participating in the sodium ion storage process. Regarding electrode materials, carbon-based substances like hard carbon and expanded-graphite exhibit promise to serve as anodes in NIBs because of the cost-effectiveness of carbonaceous materials and suitable charge/discharge plateau. …”
Section: Introductionmentioning
confidence: 99%
“…This translates into higher coordination numbers compared to typical carbonate solvents. 19 , 20 Previous studies have shown that glyme-based solvents with sodium salts have two glyme molecules complexing with the cation in the case of diglyme and triglyme systems, and one to two distinct glyme molecules in the solvation shells of tetraglyme systems. 21 The chelating effect is particularly pronounced in longer glymes resulting in increased oxidative stability.…”
Section: Introductionmentioning
confidence: 99%